Küresel çekirdeklerde quadrupol ve spin-quadrupol matris elemanlarının hesaplanması - Kahriman, Bilal (Muş Alparslan Üniversitesi, 2021)
Küresel çekirdeklerde mulltipol operatörleri kullanılarak, QRPA yaklaşımı çerçevesinde, Quadrupol ve Spin-Quadrupol matris elemanları elde edilmiştir. Elde edilen matris elemanları bu çalışmanın ekinde verilen FORTRAN77 programıyla 90Zr çekirdeği için hesaplanmıştır.

Quadrupol and Spin-Quadrupol matrix elements were obtained within the framework of the QRPA approach using mulltipol operators in spherical nuclei. The obtained matrix elements were calculated for the 90Zr nucleus with the FORTRAN77 program given in the appendix of this study.
Calculation of quadrupole and spin-quadrupole matrix elements in spherical nuclei
Keywords: Fizik ve Fizik Mühendisliği; Physics and Physics Engineering